Mappianthus kachinensis (Icacinaceae), a new woody climber from Kachin State, Myanmar - Utteridge, Timothy M. A.; Aung, Mu Mu; Wheatcroft, Hannah; Plummer, Jack; Armstrong, Kate E. (Thai Forest Bulletin (Botany), 2025)
Mappianthus kachinensis, a new species currently only known from Kachin State, Putao District, northern Myanmar, is described and illustrated. A detailed description along with etymology, conservation status, and a line illustration are provided for a new species. The genus is still poorly known, and this discovery increases the number of species in Mappianthus to at least three. Problems with species delimitation in the genus are also briefly discussed.